Successful ablation of coexistent mahaim tachycardia and right posterior accessory pathway in a patient with Ebstein's anomaly - Gül, Enes Elvin; Akdeniz, Celal; Tuzcu, Volkan (Turkish Soc Cardiology, 2016)
The atriofascicular accessory pathway (AP), known as the Mahaim pathway, is a rare form of pre-excitation, comprising less than 3% of all APs. Mahaim AP is characterized by decremental, anterograde-only conduction, and antidromic tachycardia with left bundle branch morphology. Prevalence of Mahaim AP in Ebstein's anomaly is significantly high. In addition, combination of Wolff-Parkinson-White (WPW) syndrome and Mahaim AP in patients with Ebstein's anomaly has been reported. Presently described is the coexistence of Mahaim AP and manifest WPW syndrome in a patient with Ebstein's anomaly, who was successfully ablated without fluoroscopy.

Atriyofasiküler aksesuvar yolak (AY) diğer deyimle Mahaim yolakları preeksitasyonun nadir formu olup aksesuvar yolakların %3’den daha azını oluşturmaktadır. Mahaim aksesuvar yolak dekremental, sadece önedoğru iletisi olan ve sol dal bloklu antidromik taşikardi ile kendini gösterir. Mahaim aksesuvar yolağın Ebstein anomalisindeki prevalansı oldukça yüksektir. Ayrıca Wolf-Parkinson-White (WPW) sendromu ve Mahaim AY birlikteliği Ebstein anomalisinde gösterilmiştir. Bu yazıda, Ebstein anomalisi olan hastada WPW ve Mahaim AY birlikteliğinin floroskopisiz başarılı ablasyonunu sunuyoruz.
Ebstein anomalisi olan çocukta Mahaim taşikardi ve sağ arka aksesuvar yol birlikteliğinin başarılı ablasyonu
WOS: 000380170200012
PubMed ID: 27439929
Keywords: Accessory Pathway; Ebstein's Anomaly; Mahaim Pathway; Aksesuar Yolak; Ebstein Anomalisi; Mahaim Yolağı